Optimization of small and very small long life Pb-Bi Cooled Fast reactors - Zaki Su’ud (Indonesian Journal of Physics, 2004)
In this paper optimization of small and very small nuclear power plant is discussed. The reactor is subjected to fulfill fourth generation nuclear power plant criteria. For very small nuclear power reactor, constraining the reactivity swing to be smaller than one dollar during operation usually result in small power density, relatively large core and low burnup level. One key concept in the present discussion is by the use of tight lattice and large fuel diameter so that the fuel volume fraction becomes large and pressure drop is still reasonable. The central part of the core is filled by fertile material for minimization of excess reactivity during reactor operation. By using this concept small but effective nucclear power plant can be designed. The core can achieve burnup of about 13 % heavy metal and the height and diameter of the active core is much smaller than 1 meter.